Peran Entrepreneurial Branding dalam Membentuk Persepsi dan Loyalitas Konsumen: Sebuah Studi Literatur - Febrianto Saputra; Ahmad Agus Eko Wahyudi; Rusnandari Retno Cahyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the role of entrepreneurial branding in shaping consumer perceptions and loyalty through a literature review approach. The background is driven by increasing business competition that requires entrepreneurs to build brands that are not only recognized but also capable of creating emotional bonds with consumers. Entrepreneurial branding emerges as a strategy that combines entrepreneurial spirit with dynamic and innovative brand management. The method used is a systematic literature review of relevant journal articles, books, and proceedings, obtained only from the Google Scholar database. The results show that entrepreneurial branding plays a significant role in shaping positive consumer perceptions through unique brand stories, authenticity, and active entrepreneur involvement. These positive perceptions subsequently contribute to increased consumer loyalty, as indicated by repeat purchases, word-of-mouth recommendations, and resilience against competing brands. The conclusion confirms that entrepreneurial branding is a key factor in building long-term relationships between brands and consumers. This study recommends that small and medium enterprises adopt entrepreneurial branding as a differentiation and loyalty enhancement strategy.